EVALUASI PELAKSANAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT PROGRAM PENGEMBANGAN KECAMATAN DI KECAMATAN NOYAN KABUPATEN SANGGAU - Abang Suriyanto (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2009)
This research aims at analyzing the implementation of the National Community Empowerment Program Implementation (PNPM) through Sub-district Development Program (PPK) at Noyan Sub-district, Sanggau District, West Borneo. The analysis covers the inputs and outputs of the program. The inputs consist of socialization, inter-village consensus, trainings, social and economic infrastructure development, saving and loan groups, and the sustainability of the program. The outputs include decreasing poverty, the expansion of income generating activity, people participation in income generating activity, the improvement of group awareness, and theimprovement of community capacity. The results of interviews, observation, and literature study show that the implementation of the National Community Empowerment Program Implementation (PNPM) through Sub-district Development Program (PPK) at Noyan Sub-district, Sanggau District, West Borneo is yet to be optimized.